Transition and diversity in rural housing provision: the case of Narrogin, Western Australia - Jones, Roy; Tonts, M. (Routledge, 2003)
The purpose of this paper is to examine the changing dynamics of housing markets in an Australian rural community. With reference to the case of Narrogin, Western Australia, it argues that there is an increasing disjuncture between the social and demographic characteristics of rural residents and the modal form of housing in country towns, namely the detached family house. Factors contributing to this disjuncture include the ageing of the population, the loss of traditional blue-collar employment, sub-regional restructuring of service provision, retirement migration patterns, and growing acceptance of the particular housing needs of groups such as the aged, the disabled, young and indigenous people. While it is clear that there is currently something of a mismatch between the characteristics of the population and the housing stock in Narrogin, it is also evident that a combination of political, cultural and economic factors form a significant barrier to adjustment in the local housing market.